Pengembangan Lms Berbasis Moodle Dengan Model Project-Based Learning Meningkatkan Kompetensi System Administrator Dan Berpikir Kritis Siswa Kelas XI Tkj Smks Wijaya Putra Surabaya - Abdilbar Ainur Ridla; Bambang Sujatmiko (Jurnal Ilmu Teknologi Informasi Indonesia, 2026)
This study aims to develop and test the effectiveness of a Moodle-based Learning Management System (LMS) named "Abdilbar Learning Space," integrated with the Project-Based Learning (PjBL) model. The research addresses the low critical thinking skills and independence of 26 class XI TKJ students in solving technical problems during the System Administrator subject. Using the ADDIE Research and Development (R&D) model, the process included Analysis, Design, Development, Implementation, and Evaluation stages. Expert validations yielded highly feasible results: 96.67% for media, 89.7% for teaching modules, 98.18% for learning materials, and 97.27% for test items. Black box testing confirmed all functions operated correctly. The implementation proved effective, showing a significant increase in cognitive competence; the average score rose from 50.38 (pre-test) to 88.65 (post-test) with an N-Gain of 0.7598 (high category) and a Wilcoxon significance value of p < 0.001. Psychomotor skills also showed excellent achievement with an average project completion score of 95.00. In conclusion, the Moodle-based LMS with a PjBL approach is valid and effective in improving students' cognitive and psychomotor competencies.